A Typology of Stakeholders and Guidelines for Engagement in Transdisciplinary, Participatory Processes - Newton, Alice; Elliott, Michael (Frontiers in Marine Science, 2016)
This paper fulfils a gap in environmental management by producing a typology of stakeholders for effective participatory processes and co-design of solutions to complex social–environmental issues and then uses this typology for a stepwise roadmap methodology for balanced and productive stakeholder engagement. Definitions are given of terminology that is frequently used interchangeably such as “stakeholders,” “social actors,” and “interested parties.” Whilst this analysis comes from a marine perspective, it is relevant to all environments and the means of tackling environmental problems. Eleven research questions about participative processes are addressed, based on more than 30 years of experience in water, estuarine, coastal, and marine management. A stepwise roadmap, supported by illustrative tables based on case-studies, shows how a balanced stakeholder selection and real engagement may be achieved. The paper brings these together in the context of several up-to-date concepts such as complex, nested governance, the 10 tenets for integrated, successful, and sustainable marine management, the System Approach Framework and the evolution of DPSIR into DAPSI(W)R(M) framework. Examples given are based on the implementation of the Marine Strategy Framework Directive, the Water Framework Directive, the Environmental Impact Assessment Directive, the Framework Directive for Maritime Spatial Planning, as well as for Regional Sea Conventions. The paper also shows how tools that have been developed in recent projects can be put to use to implement policy and maximize the effectiveness of stakeholder participation.